2016
DOI: 10.1038/ncomms13799
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating structure selection in the hydrothermal growth of FeS2 pyrite and marcasite

Abstract: While the ab initio prediction of the properties of solids and their optimization towards new proposed materials is becoming established, little predictive theory exists as to which metastable materials can be made and how, impeding their experimental realization. Here we propose a quasi-thermodynamic framework for predicting the hydrothermal synthetic accessibility of metastable materials and apply this model to understanding the phase selection between the pyrite and marcasite polymorphs of FeS2. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 50 publications
2
67
1
Order By: Relevance
“…Slightly lower γ values for pyrite (Kitchaev and Ceder, 2016) than for vaesite (Zheng et al, 2015) would however imply a lower activation energy for the nucleation of pyrite than for vaesite and can thus not be invoked to explain the faster nucleation of Ni-doped pyrite compared to Ni-free pyrite.…”
Section: Resultsmentioning
confidence: 99%
“…Slightly lower γ values for pyrite (Kitchaev and Ceder, 2016) than for vaesite (Zheng et al, 2015) would however imply a lower activation energy for the nucleation of pyrite than for vaesite and can thus not be invoked to explain the faster nucleation of Ni-doped pyrite compared to Ni-free pyrite.…”
Section: Resultsmentioning
confidence: 99%
“…The study concluded that both marcasite and pyrite were formed from pyrrhotite by a dissolution-reprecipitation mechanism regardless of crystallographic relationship. More recently, the manner that pH influences the phase formed was investigated using ab initio calculations [28]. This Figure 6.…”
Section: Nickel Concentrate Leachingmentioning
confidence: 99%
“…The nucleation kinetics influences the system at this stage of growth that is within the scope of classical nucleation theory. The phase selection in pyrite‐marcasite system can be elucidated by the surface stability of the pyrite‐marcasite phases as a function of ambient pH within nano‐size regimes relevant to nucleation under hydrothermal conditions …”
Section: Nanocrystalline Pyritementioning
confidence: 99%